Business taxation and financial decisions - Schanz, Deborah (Springer eBooks., 2011)
Managerial decisions are considerably influenced by taxes: e.g. the choice of location, buying or leasing decisions, or the proper mix of debt and equity in the company's capital structure increasingly demand qualified employees in an economic environment that is becoming more and more complex. Due to the worldwide economic integration and constant changes in tax legislation, companies are faced with new challenges ? and the need for information and advice is growing accordingly. This book's goal is to identify and quantify possible tax effects on companies' investment strategies and financing policies. It does not focus on details of tax law, but instead seeks to address students and practitioners focusing on corporate finance, accounting, investment banking and strategy consulting.